(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Background: Since angiogenesis is an integral component in tumor formation and metastasis, it constitutes a promising anti-cancer target. Betanin is a plant pigment obtained from Beta vulgaris, known for its antioxidant and anticancer properties. Hence, it is theorized that the green synthesis of silver nanoparticles with betanin (Bet-AgNPs) may confer additional biological efficacy through increased stability and uptake. Objective: To investigate the antiangiogenic and anticancer effects of Betanin-derived silver nanoparticles by CAM assay, ROS analysis, and gene expression profiling of angiogenesis marker genes. Methods: Bet-AgNPs were synthesized by green chemistry using betanin and characterized by UV–Vis spectroscopy, FTIR, and SEM. Antiangiogenic activity was tested by CAM assay by analyzing vascular morphology, count of vessels, and percent inhibition at 0 and 4 h after treatment. Intracellular ROS were measured in KB oral cancer cells by DCFH-DA staining. Expression of VEGFA, VEGFR2, HIF-1α, THBS1, and ANGPTL4 was quantified by qRT-PCR in CAM tissues treated with 20 µg/mL Bet-AgN Results: Characterization evidenced the formation of spherical, stable BetAgNPs of size 20–50 nm. CAM assay revealed a decrease in vessel branching and vessel density in a dose-dependent manner, with a strong avascular zone in the 20 µg/mL Bet-AgNP group. Quantitative analysis yielded a significant reduction in vessel count and a substantial inhibition percentage in the Bet-AgNP groups. ROS analysis in KB cells evidenced an increase in oxidative stress with the increase of nanoparticle concentration. The gene expression studies confirmed a significant downregulation of VEGFA, VEGFR2, and HIF-1α, while the antiangiogenic markers THBS1 and ANGPTL4 were upregulated. Conclusion: The Bet-AgNPs inhibited angiogenesis and expression of angiogenesis-related genes and induced ROS to exert their antiangiogenic and anticancer activities. Of course, these encouraging results motivated the use of Bet-AgNPs as a natural and biocompatible agent for therapeutic action in the inhibition of angiogenesis during cancer treatment.